Sema3a as a Novel Therapeutic Option for High Glucose-Suppressed Osteogenic Differentiation in Diabetic Osteopathy - Zhang, Lixia; Zheng, Lili; Li, Chong; Wang, Zhifang; Li, Shan; Xu, Lijun (Frontiers in Endocrinology, 2019)
Objective: Diabetic osteopathy is a common comorbidity of diabetes mellitus, with skeletal fragility, osteoporosis and bone pain. The aim of the present study was to highlight the role of sema3a on osteoblast differentiation of MC3T3-e1 in high-glucose condition and explore its therapeutic effect of diabetic osteopathy in vitro and vivo. Methods: In this study, the effect of sema3a on osteoblast differentiation in high-glucose condition was evaluated by analyzing the expression of osteogenesis-related maker including ALP, OCN, OPG, β-catenin and Runx2, as well as ALP and Alizarin Red S staining in MC3T3 osteoblastic cells. In diabetic animal model, the expression of serum bone metabolic markers, such as ALP, P1NP, OCN and β-CTX, were analyzed and micro-CT was used to detect bone architecture including Tb.N, Tb.Th, Tb.Sp, Tb.Pf, BS/BV and BV/TV after the treatment of sema3a. Results: High glucose significantly inhibited osteogenic differentiation by decreasing the expression of osteogenesis-related makers, sema3a and its receptor of Nrp-1 in a dose-dependent manner in MC3T3. In high-glucose condition, exogenous sema3a (RPL917Mu01) increased the expression of ALP, OCN, OPG, Runx2 and β-catenin in MC3T3, as well as the positive staining of ALP and Alizarin Red S. In addition, in diabetic animal model, exogenous sema3a could increase bone mass and bone mineral density, and downregulate the expression of ALP, P1NP, OCN and β-CTX. Conclusion: High glucose suppresses osteogenic differentiation in MC3T3 and sema3a may take part in this process. The application of exogenous sema3a alleviates high glucose-induced inhibition of osteoblast differentiation in diabetic osteopathy.